Immigration and the sources of strength in US foreign policy: a study in the approaches to construction and employment - Khudair , Majed Hamid; Dawood, Ban Fawzi (The International and Political Journal, 2023)
Immigration has a clear impact on the overall of the American political system, as well as on the emergence of the state and before it the states or colonies, and then it also has a major impact on the American foreign policy in terms of political thought, discourse and message adopted by the delivery of American political institutions supporting American foreign policy such as U. S Agency for international Development, not to mention on the American national security council. Hence, we are now in front of a foreign policy of a country that adopts a scientific thought in all political, economic, social and cultural fields, a country that does not fill in borders or international strategies and determinants, a country that wants to be the world and the world is America submit. Then our research comes to study the issue of immigration and clarify the strengths in American foreign policy and know what extent the phenomenon of immigration contributed to the formation of the foundations and determinants of this foreign policy submit.